Forage selection preferences of experienced cows and naïve heifers grazing native tallgrass range during winter - Aubel, N.A.; Edwards, L.N.; Eckerle, G.J.; Pacheco, L.A.; Olson, K. C.; Jaeger, John R.; Blasi, Dale A.; Murray, Leigh W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Estimating the nutritive value of a grazing animal’s diet is a significant challenge. Description of the botanical composition of a grazed diet is vital in that regard. Microhistological analysis of fecal material has been used for estimating the botanical composition of wild and domestic ungulate diets since first described by Baumgartner and Martin in 1939. Little research has been conducted on the diet selection preferences of multiparous beef cows compared to primiparous beef cows. We hypothesized that foraging strategies change as cows age. To that end, our objective was to characterize differences in diet selection between experienced multiparous and naïve primiparous beef cows grazing dormant, native tallgrass pastures during winter.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Forage; Heifers; Tallgrass range